On economists as policy advisors with applications to Switzerland - Aymo Brunetti (Swiss Journal of Economics and Statistics, 2018)
This paper analyses the role of economists in advising political agents. Based on the experience in the recent financial crisis, it starts with the important role of expectations management. Economists should make clear that precise forecasts are not possible but that application of economic principles and careful analysis of data and historical events can substantially improve political decisions. In order to be effective, economic advisors have to be aware of the first best as well as of the political feasibility of proposals. Efficiency is the obvious benchmark, but a large part of policy advice is about finding the least inefficient of the feasible alternatives. The paper argues that a crucial precondition for being an effective policy advisor are communication skills; academics who become policy advisors should not try to impress their peers but rather translate insights in a language that is understandable for educated laypeople. The paper then looks at the special situation of economic policy advice in the Swiss direct democracy before concluding with a summary of the most important preconditions for being a successful policy advisor.
Keywords: 330